(untitled) (African Journal of Public Administration & Management, 2026)
The study examines the programme implementation fidelity and the mutual benefits in the Malawi Government Graduate Internship Programme (GIP). It is premised on the basis that the Malawian Ministry of Labour has been implementing the programme since 2018, reaching out to 20232 young graduates aged 35 and below with the aim of enhancing youth employability. Using a mixed methods approach, the study sought to determine whether the programme is being implemented as per its design and to examine the value that it brings to both interns and the MDAs that host them. The study found that the programme is doing relatively well in terms of exposing interns to skills, knowledge, and expertise; however, most of the skills are administrative in nature. The recommendations from the study include enhancing monitoring and evaluation of the program, harmonization of orientation components for interns, revising the program length, and ensuring all key stakeholders are conversant with the guidelines. These recommendations are relevant not only to Malawi’s public service programming with regard to youth employment but also to other African nations seeking to come up with strategies for the same.